2020
DOI: 10.32872/spb.2873
|View full text |Cite
|
Sign up to set email alerts
|

Motivated behavior in intimate relationships: Comparing the predictive value of motivational variables

Abstract: Motivational variables are considered fundamental factors influencing the occurrence of behavior. The current study compared different types of motivational variables (implicit and explicit motive dispositions, motivation as states and as aggregated person-level variables) in their ability to predict communal and agentic behavior reports in intimate relationships. 510 individuals completed measures of dispositional communion and agency motives and participated in a dyadic experience sampling study with five as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
(99 reference statements)
1
7
0
Order By: Relevance
“…Further, the current findings add to existing evidence of the relevance of both implicit and explicit motives for relationship functioning (e.g., Hagemeyer et al, 2013a ; Zygar-Hoffmann et al, 2020b ). In the current investigation, both implicit and explicit communal motives predicted communal behavior in interaction with perceived communal partner behavior.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Further, the current findings add to existing evidence of the relevance of both implicit and explicit motives for relationship functioning (e.g., Hagemeyer et al, 2013a ; Zygar-Hoffmann et al, 2020b ). In the current investigation, both implicit and explicit communal motives predicted communal behavior in interaction with perceived communal partner behavior.…”
Section: Discussionsupporting
confidence: 79%
“…The present research used data from an experience sampling study with German couples. The data are available as a scientific use-file (Zygar-Hoffmann et al, 2020a ) and have been used in previous publications (Pusch et al, 2020 ; Zygar-Hoffmann and Schönbrodt, 2020 ; Zygar-Hoffmann et al, 2020b ; Schönbrodt et al, 2021 ). However, none of these previous publications addressed the hypotheses tested in the present research, but focused on other hypotheses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, researchers use dyads to examine how daily proactivity can be transmitted between colleagues (Demerouti & Peeters, 2017), how working to change one's relationship influences its quality (Young, Curran, & Totenhagen, 2013), and how providing support affects caregivers' and patients' affect (Kroemeke, Knoll, & Sobczyk-Kruszelnicka, 2019). In this Special Issue an example of dyadic design can be found in the paper by Zygar-Hoffmann et al (2020) where participants reported on their own and their partner's behaviors.…”
mentioning
confidence: 99%